2012
DOI: 10.1108/13620431211201337
|View full text |Cite
|
Sign up to set email alerts
|

The influence of general beliefs on the formation of justice expectations

Abstract: PurposeThe purpose of this paper was to investigate the influence of applicants' justice beliefs (i.e. belief in a just world and belief in tests) on justice expectations with respect to a forthcoming application for the job of prison guard. Further, it aims to study the moderating role of direct experiences on the relationship between beliefs and justice expectations.Design/methodology/approachA written survey was administered to 803 applicants, just before the start of the selection procedure. Data were self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Results support predictions, with justice expectations found to be important determinants of test-taking motivation, test efficacy, and perceptions of justice (Bell, Wiechmann, & Ryan, 2006;Chapman, Uggerslev, & Webster, 2003;Derous et al, 2004;Schreurs, Derous, Proost, & De Witte, 2010). More recently, Geenen, Proost, Schreurs, et al (2012) conducted a study to examine the source of justice expectations. Consistent with the aforementioned models (Bell et al, 2004;Derous et al, 2004), justice beliefs were significantly related to procedural and distributive justice expectations.…”
Section: Expanded Theoretical Focusmentioning
confidence: 54%
See 1 more Smart Citation
“…Results support predictions, with justice expectations found to be important determinants of test-taking motivation, test efficacy, and perceptions of justice (Bell, Wiechmann, & Ryan, 2006;Chapman, Uggerslev, & Webster, 2003;Derous et al, 2004;Schreurs, Derous, Proost, & De Witte, 2010). More recently, Geenen, Proost, Schreurs, et al (2012) conducted a study to examine the source of justice expectations. Consistent with the aforementioned models (Bell et al, 2004;Derous et al, 2004), justice beliefs were significantly related to procedural and distributive justice expectations.…”
Section: Expanded Theoretical Focusmentioning
confidence: 54%
“…The hiring expectations of applicants and their investment in the selection process have been cited as likely to affect applicant reactions, although until recently this has received little attention. Geenen, Proost, Schreurs, et al (2012) found that the test-taking experience can enhance the relationship between belief in tests and justice expectations. Similarly, Reeder, Powers, Ryan, and Gibby (2012) found that job familiarity and prior success affected applicants' face validity perceptions of a test.…”
Section: Selection Contextmentioning
confidence: 99%
“…Drawing upon social exchange theory (SET) that focuses on the reciprocation process of the perceived mutual obligation between employees and their organizations, employees are found to direct their acts of reciprocity to the degree to which they perceive their organization to be committed to them (Eisenberger et al, 1986). In this context, employees who experience distributive justice are more likely to commit themselves to their organization since they perceive that they are receiving sufficient return on their invested resources (Mattila and Patterson, 2004;Geenen et al, 2012). From a SET perspective, employees' perceptions that their efforts at work are fairly reciprocated by the organization in terms of adequate compensation lead to further affective commitment to their organization (He and Brown, 2013).…”
Section: Organizational Justice and Affective Organizational Commitmentmentioning
confidence: 99%
“…Applicants' subsequent attitudes, intentions, and behaviors are significantly and meaningfully influenced by their responses throughout the selection process. According to certain research, an applicant's unfavorable response could set off a chain reaction of unfavorable events that could include decreased organizational attitudes (like low organizational attractiveness), unwanted behaviors or behavioral intentions (like referral and litigation intentions) [17], and even an impact on the applicant's actual acceptance of a job offer as opposed to just the expected acceptance [18]. In addition, negative reactions can also shorten an applicant's attention span [19], which might result in poor performance during the interview.…”
Section: Applicants and Fairness Perceptionmentioning
confidence: 99%